Glimpses of Tibetan divination: past and present - Maurer, Petra; Rossi, Donatella; Scheuermann, Rolf (Prognostication in history, 2019)
Front Matter -- Copyright Page -- Preface -- Background History of the Volume -- On the Contributions Contained in This Volume -- Notes on Contributors -- A Case of Prophecy in Post-imperial Tibet /Per Kværne -- Three Dice, Four Faces, and Sixty-Four Combinations: Early Tibetan Dice Divination by the Numbers /Brandon Dotson -- A Preliminary Analysis of Old Tibetan Dice Divination Texts /Ai Nishida -- Divinations Padampa Did or Did Not Do, or Did or Did Not Write /Dan Martin -- Landscaping Time, Timing Landscapes: The Role of Time in the sa dpyad Tradition /Petra Maurer -- Signs and Portents in Nature and in Dreams: What They Mean and What Can Be Done about Them /Charles Ramble -- Identifying the Magical Displays of the Lords of the World: The Oneiromancy of the gSal byed byang bu /Donatella Rossi -- Vibhūticandra’s Svapnohana and the Examination of Dreams /Rolf Scheuermann -- Prognosis, Prophylaxis, and Trumps: Comparative Remarks on Several Common Forms of Tibetan Cleromancy /Alexander K. Smith -- The Role of Lamyn Gegeen Blo bzang bstan ’dzin rgyal mtshan in the Dissemination of Tibetan Astrology, Divination and Prognostication in Mongolia /Agata Bareja-Starzyńska -- Back Matter -- Index.